Heterologous production of Chondroitin - Couto, Márcia R. (2022)
Chondroitin sulfate (CS) is a glycosaminoglycan with a broad range of applications being a popular dietary supplement for osteoarthritis. Usually, CS is extracted from animal sources. However, the known risks of animal products use have been driving the search for alternative methods and sources to obtain this compound. Several pathogenic bacteria naturally produce chondroitin-like polysaccharides through well-known pathways and, therefore, have been the basis for numerous studies that aim to produce chondroitin using non-pathogenic hosts. However, the yields obtained are not enough to meet the high demand for this glycosaminoglycan. Metabolic engineering strategies have been used to construct improved heterologous hosts. The identification of metabolic bottlenecks and regulation points, and the screening for efficient enzymes are key points for constructing microbial cell factories with improved chondroitin yields to achieve industrial CS production. The recent advances on enzymatic and microbial strategies to produce non-animal chondroitin are herein reviewed. Challenges and prospects for future research are also discussed.